Pendidikan Humanisme dalam Sekolah Ramah Anak Perspektif Al-Qur’an - Dariyanto, Dariyanto; Fajar , Abbas Sofwan Matla'il (JOM, 2024)
This study aims to affirm how the Qurán explains humanist education in Child-Friendly Schools (CFS). Humanistic education seeks to create education that humanizes students by building harmonious communication. The Child-Friendly Schools program was initiated by UNICEF and responded to by the state Ministry of Women's Empowerment and Child Empowerment with policy No. 8 of 2014. The cases of violence and bullying of students in schools are a social problem that still occurs. The tahlili interpretation method is used to interpret the values ​​of humanist education in CFS. This study uses the library research method with qualitative descriptive analysis techniques. As a result, the Qur'an affirms the importance of realizing the essence of feeling safe and comfortable in the educational environment by emphasizing getting to know each other to live in peace, harmony, and tolerance. These attitudes support the learning and teaching process and can encourage students to have noble character. Thus, getting to know each other, taáruf between school members, especially between students, is an important principle to create a sense of security and comfort in the school environment.